IMPLEMENTASI PENDIDIKAN KARAKTER SEBAGAI BASIS PENINGKATAN MUTU PENDIDIKAN DI SDIT AL-JABAR GONDANG SRAGEN - Sumarno, Sumarno; Nurcahyadi, Andik (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Character education is an effort to shape human personality for the better. This study used a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The results of this study reveal that in the implementation of character education at SDIT Al-Jabar Gondang through three implementation guidelines, namely: first, the method of implementation; second, implementation in schools consisting of: a) daily activities in class; b) school culture; c) activities at school. The characters achieved include; discipline, diligence, responsibility, care, cooperation, tolerance, confidence, courage. Keywords: education, character, values, SDIT Al-Jabar